The role of extracorporeal membrane oxygenation in adult kidney transplant patients: A qualitative systematic review of literature. Issue 1 (20th August 2022) - Reid, Trista D.; Kratzke, Ian; Dayal, Diana; Raff, Lauren; Serrano, Pablo; Kumar, Aman; Boddie, Olivia; Zendel, Alex; Gallaher, Jared; Carlson, Rebecca; Boone, Joshua; Charles, Anthony G.; et al.
Abstract: Background: A paucity of evidence exists regarding the risks and benefits of Extracorporeal Membrane Oxygenation (ECMO) in adult kidney transplantation. Methods: This was a systematic review conducted from Jan 1, 2000 to April 24, 2020 of adult kidney transplant recipients (pre‐ or post‐ transplant) and donors who underwent veno‐arterial or veno‐venous ECMO cannulation. Death and graft function were the primary outcomes, with complications as secondary outcomes. Results: Twenty‐three articles were identified that fit inclusion criteria. 461 donors were placed on ECMO, with an overall recipient 12‐month mortality rate of 1.3% and a complication rate of 61.5%, the majority of which was delayed graft function. Fourteen recipients were placed on ECMO intraoperatively or postoperatively, with infection as the most common indication for ECMO. The 90‐day mortality rate for recipients on ECMO was 42.9%, with multisystem organ failure and infection as the ubiquitous causes of death. 35.7% of patients experienced rejection within 6 months of decannulation, yet all were successfully treated. Conclusions: ECMO use in adult kidney transplantation is a useful adjunct. Recipient morbidity and mortality from donors placed on ECMO mirrors that of recipients from standard criteria donors. The morbidity and mortality of recipients placed on ECMO are also similar to other patient populations requiring ECMO. Abstract : Systematic review of adult kidney transplant patients placed on ECMO demonstrates similar complication rates to other patient populations requiring ECMO.